2013
DOI: 10.1177/147470491301100113
|View full text |Cite
|
Sign up to set email alerts
|

Friends with Benefits, but without the Sex: Straight Women and Gay Men Exchange Trustworthy Mating Advice

Abstract: Although research has made progress in elucidating the benefits exchanged within same- and opposite-sex friendships formed between heterosexual men and women, it is less clear why straight women and gay men form close relationships with one another. The current experiments begin to address this question by exploring a potential benefit hypothesized to be uniquely available to straight women and gay men in the context of these friendships: trustworthy mating advice. Experiment 1 revealed that straight women per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
5
23
0
Order By: Relevance
“…It appears that committed gay men, just like committed straight women, continue to seek emotional closeness from straight female friends. This is consistent with other research highlighting the uniquely beneficial friendships between gay men and straight women (Russell et al, ; Shepperd et al, ) compared to friendships between lesbians and straight men (Muraco, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It appears that committed gay men, just like committed straight women, continue to seek emotional closeness from straight female friends. This is consistent with other research highlighting the uniquely beneficial friendships between gay men and straight women (Russell et al, ; Shepperd et al, ) compared to friendships between lesbians and straight men (Muraco, ).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with research showing heterosexual men are more likely to disclose to and have higher expectations for female interaction partners than male interaction partners (Fuhrman et al, 2009;Hill & Stull, 1987), this study found that gay men have higher expectations for their straight female friends than for their gay male friends. Consistent with research showing that women rate their same-sex friendships higher than men rate theirs (Dindia & Allen, 1992;Kuttler & La Greca, 2004), and that gay men rely on straight women more than gay men for mating advice (Russell et al, 2013), this study found that lesbians had higher expectations for their gay female friends than for their straight male friends, and gay men had higher expectations for their straight female friends than lesbians did for their straight male friends.…”
Section: Behavioral Expectations For Friendssupporting
confidence: 85%
See 2 more Smart Citations
“…Heterosexual women have also reported that they feel better about themselves when they spend time with gay male friends (Barlett, Patterson, VanderLaan, & Vasey, 2009) and they trust the honest advice of their gay friends more than the advice from other women (Russell, DelPriore, Butterfield, & Hill, 2013). Women also tend to score higher on a measure called the homopositivity scale, which measures positive stereotypes of gay men's warmth including items like, "Gay men are more in touch with their emotions than straight men."…”
Section: Stereotypes Of Gay Men and Lesbiansmentioning
confidence: 99%